LIVING SUNNAH â€œTRADISI DZIKIR 7 LAKSAâ€ PERSPEKTIF TASAWUF - Muhammad Aminudin; Dzikri Nirwana; Saifuddin Saifuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Antasari Banjarmasin, 2025)
Abstract: Dhikr is an important spiritual practice in Islam that connects the servant with Allah SWT both outwardly and inwardly. One of the dhikr traditions that has developed strongly in the Nusantara region, especially in South Kalimantan, is the â€œdzikir 7 laksa,â€ which involves reciting the tahlil phrase â€œLÄ ilÄha illÄ AllÄhâ€ 70,000 times. This article examines dzikir 7 laksa from a Sufi perspective by studying its scriptural basis and spiritual wisdom. Through the study of classical texts and the stories of Sufi scholars such as Sheikh Ibn â€˜Arabi and Sayyid Muhammad Amin Kutbi, dzikir 7 laksa is understood not merely as a ritual for atonement but also as a process of purifying the heart (tazkiyatun nafs) and a path towards the knowledge of Allah (maâ€˜rifatullah). This practice has a strong social dimension in strengthening Islamic brotherhood (ukhuwah Islamiyah) within the community. A qualitative method with literature review is used to describe and analyze the meaning and function of dzikir 7 laksa as a manifestation of the living Sunnah among Muslims in the Nusantara. This study emphasizes the importance of preserving the tradition of dzikir as a profound spiritual heritage as well as a reinforcement of social solidarity. Keywords: 7 Laksa Dhikr, Tahlil, Sufism, Redemption of Sins, Ma'rifatullah Â Abstrak; Dzikir merupakan amalan spiritual penting dalam Islam yang menghubungkan hamba dengan Allah SWT secara lahir dan batin. Salah satu tradisi dzikir yang berkembang kuat di Nusantara khususnya Kalimantan Selatan adalah dzikir 7 laksa, yakni pengucapan kalimat tahlil â€œLÄ ilÄha illÄ AllÄhâ€ sebanyak 70.000 kali. Artikel ini mengkaji dzikir 7 laksa dari perspektif tasawuf dengan menelaah landasan dalil dan hikmah spiritualnya. Melalui kajian teks klasik dan kisah para ulama sufi seperti Syekh Ibnu â€˜Arabi dan Sayyid Muhammad Amin Kutbi, dzikir 7 laksa dipahami bukan sekadar ritual penebus dosa, tetapi juga sebagai proses penyucian hati (tazkiyatun nafs) dan jalan menuju maâ€˜rifatullah. Praktik ini memiliki dimensi sosial yang kuat dalam mempererat ukhuwah Islamiyah di masyarakat. Metode kualitatif dengan studi pustaka digunakan untuk mendeskripsikan dan menganalisis makna serta fungsi dzikir 7 laksa sebagai wujud living sunnah di tengah umat Islam Nusantara. Kajian ini menegaskan pentingnya pelestarian tradisi dzikir sebagai warisan spiritual yang mendalam sekaligus penguat solidaritas sosial. Kata Kunci: Dzikir 7 Laksa, Tahlil, Tasawuf, Penebusan Dosa, Ma'rifatullah